(untitled) (Canadian Journal of Native Studies, 2026)
Inuit Elders who have chronic health needs are removed and relocated to distant non-Inuit communities and institutions for long-term palliative and hospice care. There is an obvious systemic problem where governments with limited funding, in harsh and complex environs, are unable to provide the requisite health care, housing, and other social services and infrastructure that Inuit communities and people direly need. This essay seeks to describe the tragic irony the system of Inuit Elder long-term residential care represents. Reminiscent of Residential Schools, Inuit only can best judge how well they have progressed or achieved their goals of self-determination and self-governance.